Investasi Berbasis Syari’ah di Indonesia - Ridwan Ismail Gorib; Latifah Wulandari Asbaruna (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
The goal of this study is to establish whether existing investments in Indonesia are halal. The distinction between this study and other studies is that this study focuses on components of Sharia that need to be revisited in light of the current investments, many of which contain elements of Riba, Gharar, and even gambling. As a result, it is vital to explore the types of investments that are permissible under Islamic economic law. The normative juridical research approach will be applied in this study. Secondary data is data that is not directly given to data collectors and is gathered through books, scientific journals, and internet sites containing Sharia Investment-related content. The data gathering approach used in this study is a literature review that is closely related to the research goal and title. The goal of this study's findings is to provide a comprehensive explanation of the terminologies and principles that must be addressed when investing or practicing muamalah.